ISLAMIC EDUCATION MANAGEMENT STRATEGIES IN IMPROVING THE QUALITY OF LEARNING IN MADRASAS - Agus Fawait; Wilta Firdau Siyeh; Aslan Aslan (CV. ADIBA AISHA AMIRA, 2024)
Islamic education management is a structured approach that aims to organize, prepare, implement, and evaluate the education process in the context of Islamic values and principles. The research method used in this study is a literature study. The results reveal that careful and systematic planning, teacher competency development, a comprehensive evaluation approach, and the involvement of parents and the community are the main factors in improving the quality of learning. Good and structured planning includes developing an adaptive and relevant curriculum, so that madrasahs can provide integrated and directed education to meet the needs of students and the demands of the times. Developing teachers' competencies through training and continuing education has proven to be very effective in improving teachers' teaching skills, which in turn improves academic quality and the development of students' Islamic values. A regular evaluation approach helps in identifying the strengths and weaknesses of the learning process and outcomes, enabling the madrasah to make necessary adjustments and improvements. Finally, the involvement of parents and the community in the education process at the madrasah provides a comprehensive and integrated support for students, creating an inspiring and supportive learning environment.